Потенциометрическое определение некоторых галогенид-ионов с использованием углеродного композитного электрода - Страшко, Юлия Михайловна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
The article presents the results of using carbon composite electrode (CCE) in potentiometric titration of the solution containing Cl-, Br- and I- by the solution of silver nitrate (AgNO3). The conditions for potentiometric determination of halide ions (working concentration range, pH, supporting electrolyte, frequency ultrasound). The titration curves were processed by the linearization method. The conditions of separate determination of Cl-, Br- and I- were selected in the mixture.